EMERGENCY DEPARTMENT RE-ATTENDANCES AND TREATMENT MODIFICATIONS IN YOUNG CHILDREN WITH UNCOMPLICATED COMMUNITY-ACQUIRED PNEUMONIA: A PERUKI STUDY. Issue 12 (18th November 2016) - Bielicki, J; Sharland, M; Lyttle, M; Hartshorn, S; Petrie, J
Abstract : Objectives & Background: Data on the rate of antibiotic retreatment in children with uncomplicated community-acquired pneumonia (CAP) are lacking. We conducted a service evaluation of CAP management to review assumptions for a large UK-based trial planning to recruit children with CAP in emergency departments (EDs). The primary endpoint for the trial is the need for antibiotic retreatment, and the retreatment rate was estimated to be 5% on the basis of non-UK literature. Methods: Twenty-six EDs from Paediatric Emergency Research in the United Kingdom & Ireland (PERUKI) recorded data on the management of 1–5 year old children presenting with lower respiratory tract infection (LRTI) who were treated with antibiotics after visiting the ED. Data were collected over a 4 week period, and information was collected on any reattendance for four weeks after the index visit on all children whether they were immediately discharged from ED, or admitted to inpatient wards. Data were descriptively analyzed to identify re-attendances and antibiotic retreatment. Retreatment was defined as modification of on-going antibiotic therapy or prescription of a new antibiotic treatment course after the initial course had been completed. Results: In total, 936 patients (56% males) were included. Of these, 651 (70%) were discharged from the ED, while 285 (30%) were admitted. Of 651 immediately discharged patients, 97 (16%) had ≥1 re-attendance to the ED: 56 (9%) re-attended because of LRTI symptoms, and 28 (4%) were re-treated with antibiotics with treatment modification in 21 patients, and a new antibiotic prescription in 7 children. Of 285 admitted patients, 41 (15%) had ≥1 ED re-attendance, 29 (10%) re-attended because of LRTI symptoms, and 15 (5%) were re-treated with antibiotics. On-going antibiotic therapy was modified in only 5 patients, and new antibiotic treatment was prescribed to the remaining 10 patients. The overall re-attendance rate was 15% (138/936), the LRTI-related re-attendance rate was 9% (85/936), but the antibiotic re-treatment rate was lower at 5% (43/936, 26 modifications, 17 new prescriptions). Conclusion: Among 1–5 year-olds, representations to ED within 4 weeks of an index visit for CAP were frequent, but only 1 in 20 was retreated with antibiotics. The antibiotic retreatment rate of 5% was the same as the estimates informing trial design.